Efektivitas Edukasi Laktasi terhadap Pengetahuan dan Self Efficacy Ibu Menyusui di Puskesmas Waode Buri Buton Utara - Masluroh, Masluroh; Risnayanti, Risnayanti (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT In 2020, UNICEF stated that the coverage of exclusive breastfeeding in the world reached 38%. Meanwhile in developing countries it is only 39%. Exclusive breastfeeding coverage in ASEAN countries such as India has reached 46%, in the Philippines 34%, in Vietnam 27% and in Myanmar 24%, while exclusive breastfeeding coverage in Indonesia in 2023 will only be 73.97%. North Buton Regency achieved exclusive breastfeeding for babies at 58%. There are three reasons why many mothers stop breastfeeding, incorrect latch while breastfeeding causes the newborn to have difficulty sucking (27.1%), breast milk does not meet the baby's needs (55.6%), and mothers believe that they are not getting enough breast milk (52 .2%). The level of knowledge is closely related to the success of exclusive breastfeeding. To determine the effectiveness of lactation education on the knowledge and self-efficacy of breastfeeding mothers. Quasy experimental with a one group pretest-posttest design research type. The sample in this study was all 40 breastfeeding mothers at the Waode Buri Buton North Community Health Center, in March - July 2024, the sampling technique was total sampling. Before being given lactation education, the majority of respondents had sufficient knowledge (47.5%) and afterward had good knowledge (72.5%). Before being given lactation education, the majority of respondents had low self-efficacy (62.5%) and afterward had high self-efficacy (100%). There is effectiveness of lactation education on the level of knowledge and level of Self Efficacy of breastfeeding mothers (p value 0.000). There is the effectiveness of lactation education on the level of knowledge and level of Self-Efficacy of breastfeeding mothers. It is hoped that health workers can increase education about lactation so that breastfeeding mothers have better knowledge. Keywords: Knowledge, Self Efficacy, Lactation Education  ABSTRAK UNICEF tahun 2020 menyebutkan cakupan pemberian ASI eksklusif di dunia mencapai 38%. Sementara dinegara berkembang hanya 39%. Cakupan ASI Eksklusif di Negara ASEAN seperti India sudah mencapai 46%, di Philipina 34%, di Vietnam 27% dan di Myanmar 24%, sedangkan cakupan pemberian ASI eksklusif di Indonesia tahun 2023 hanya 73,97%. Kabupaten Buton Utara pencapaian ASI eksklusif pada bayi sebesar 58%. Ada tiga alasan mengapa banyak ibu berhenti menyusui, pelekatan yang salah saat menyusui menyebabkan bayi baru lahir kesulitan mengisap (27,1%), ASI tidak memenuhi kebutuhan bayi (55,6%), dan ibu percaya bahwa mereka tidak mendapatkan cukup ASI (52,2%). Tingkat pengetahuan sangat erat hubungannya dalam keberhasilan pemberian ASI eksklusif. Mengetahui efektivitas edukasi laktasi terhadap pengetahuan dan self efficacy ibu menyusui. Quasy eksperimental dengan jenis penelitian desain one grup pretest-postest design. Sampel dalam penelitian ini adalah seluruh ibu menyusui di Puskesmas Waode Buri Buton Utara, pada bulan Maret - Juli 2024 sebanyak 40 orang, teknik pengambilan sampel adalah total sampling. Sebelum diberikan edukasi laktasi mayoritas responden berpengetahuan cukup (47,5%) dan sesudahnya berpengetahuan baik (72,5%). Sebelum diberikan edukasi laktasi mayoritas responden dengan self efficacy rendah (62,5%) dan sesudahnya dengan self efficacy tinggi (100%). Ada efektivitas edukasi laktasi terhadap tingkat pengetahuan dan tingkat Self Efficacy ibu menyusui (p value 0,000). Ada efektivitas edukasi laktasi terhadap tingkat pengetahuan dan tingkat Self Efficacy ibu menyusui. Diharapkan tenaga kesehatan dapat meningkatkan penyuluhan tentang laktasi sehingga ibu menyusui memiliki pengetahuan yang lebih baik. Kata Kunci: Pengetahuan, Self Efficacy, Edukasi laktasi